MODERNISASI SISTEM PENDIDIKAN ISLAM DI INDONESIA PADA ABAD 21 - Syahminan Syahminan (Jurnal Ilmiah Peuradeun, 2014)
Modernization of Islamic education is an absolute demand. Everyone effort, especially teacher, lecturer, politician, stakeholder, state, or private sector surely bring positive impact to education, include Islamic education. However, education system implemented today, in school or ex-scroll, remain contain weakness and deterioration. This paradigm triggers the rise of Islam education modernization spirit. This article show how Indonesian education figure see Islamic education condition in Indonesia. Meanwhile, by and large we would about modernization Islamic education effort that more constructive ad relevant with change and development on this globalization and industrialization era.